EXAMINING THE ROLE OF FAMILY MEMBERS IN FAMILY BUYING CENTER IN ADULT HUNGARIAN POPULATION - Eva Polya; Robert Sandor Szucs (European Scientific Journal, ESJ, 2013)
In our paper we examine the role of family members in family buying center. In the first part of this paper our aim is to highlight the importance of family Buying Center examinations, introduce briefly its relevance within family purchase decision making processes. In the second part of our paper we introduce our own quantitative research results oriented on family Buying Center and roles undertaken by different family members.